KONSEPSI PENDIDIKAN ISLAMI PADA ANAK USIA DINI - M. Yemmardotillah (El-Rusyd, 2017)
Children are a mandate that is deposited with by Allah to every parent. As a mandate, then the child should be maintained, protected, cared for and educated well and give a strong foundation of faith and properly so that they grow up to be people who build, not ruin. Son of a baby, light eyes, a beacon of hope, the center of family pride as well as the mandate given Allah to each parent as well as a test that God gave parents. Therefore, they should be educated early as possible. Islamic education in early childhood is needed to good morals for children in the future. In this respect the role of parents and teachers is needed in educating and guiding children toward a favor by giving learning good and proper, because the early childhood is the golden age, where children are able to permeate all learning life exemplified the surrounding environment will be the foundation for his future. If Islamic education has inculcated early, expected to be born in successive having high science and good morals so that our nation will become a developed and civilized.